Integrasi Etnis Tionghoa dengan Penduduk Lokal di Wonosobo Tahun 1970 sampai 1998 - Aldi Hendra Pratama (Pusat Riset dan Inovasi Nasional, 2024)
Even though they are dominant in the economic sector, it does not always make it easy for Chinese citizens to survive among local ethnic groups and they must always adapt to various changes in power. This can be seen by the presence of racism entering the Soeharto regime and peaking during the reform period in 1998 which was marked by the amount of violence experienced by the Chinese people. This research is limited temporally, namely from 1970 when development was experiencing very rapid progress during the New Order era until 1998 with the peak event, namely riots and violence experienced by almost all Tonghoa people in Indonesia. Apart from that, the spatial boundary used is Wonosobo City because it is a place for the Chinese community. The aims of this research are (1) to reveal the forms of relations with local communities in the lives of the Chinese people in the 1970s (2) to find out the role played by ethnic Chinese in the development of Wonosobo City during the New Order era (3) to reveal the riots in May 1998 and the racism that occurred happened to Chinese residents in Wonosobo (4) knowing about the efforts made to stop racism that occurred in 1998. Historical research methods were used to obtain data from primary and secondary sources. Primary sources were obtained through archives, newspapers and interviews with related parties. Meanwhile, secondary sources are obtained through literature studies in books, journals, articles and others related to the research topic. Even though during the New Order era there was racism and restrictions on the rights of Chinese citizens. In Wonosobo itself, no significant incidents occurred, including when it peaked in 1998. This is due to the high level of tolerance among religious communities and Wonosobo residents.